(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
Semantic marking allows you to identify the semantics of lexical units in corpus texts and determine their multiple meanings or homonyms in existing cases. Semantic analysis is one of the main natural language processing (NLP) processes that is carried out on a corpus using these semantic tags and presented to the user in the form of a semantic annotation. This article discusses the importance of semantic tagging of linguistic units in Uzbek language corpora, the development of a system for semantic tagging of corpora and semantic annotation.